2016
DOI: 10.1016/j.jqsrt.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

A room temperature CO2 line list with ab initio computed intensities

Abstract: Atmospheric carbon dioxide concentrations are being closely monitored by remote sensing experiments which rely on knowing line intensities with an uncertainty of 0.5% or better. We report a theoretical study providing rotationvibration line intensities substantially within the required accuracy based on the use of a highly accurate ab initio dipole moment surface (DMS). The theoretical model developed is used to compute CO 2 intensities with uncertainty estimates informed by cross comparing line lists calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 58 publications
(81 reference statements)
11
129
0
Order By: Relevance
“…Although TCCON is not a solely HITRAN-based analysis (Wunch et al, 2011), a correction factor of 0.9898 for CO 2 , 0.9765 for CH 4 , and 1.0183 for H 2 O (Wunch et al, 2010) is needed to bring the overall TCCON retrievals into agreement with the WMO-based data. Additionally, theoretical calculations by (Zak et al, 2016) found an approximately 0.5% difference between CO 2 line parameters from HITRAN 2012 and their density functional theory calculations and an additional 0.5% difference between the calculations and new measurements by (Devi et al, 2016) in the 1.6-micron region. Certainly this discrepancy between retrievals from HITRAN and WMO-calibrated instruments is not fundamental and further experimental work should lead to improved spectral database parameters and much better agreement.…”
Section: Intercomparison Results and Discussionmentioning
confidence: 94%
“…Although TCCON is not a solely HITRAN-based analysis (Wunch et al, 2011), a correction factor of 0.9898 for CO 2 , 0.9765 for CH 4 , and 1.0183 for H 2 O (Wunch et al, 2010) is needed to bring the overall TCCON retrievals into agreement with the WMO-based data. Additionally, theoretical calculations by (Zak et al, 2016) found an approximately 0.5% difference between CO 2 line parameters from HITRAN 2012 and their density functional theory calculations and an additional 0.5% difference between the calculations and new measurements by (Devi et al, 2016) in the 1.6-micron region. Certainly this discrepancy between retrievals from HITRAN and WMO-calibrated instruments is not fundamental and further experimental work should lead to improved spectral database parameters and much better agreement.…”
Section: Intercomparison Results and Discussionmentioning
confidence: 94%
“…It would appear that this dependence is induced from the work of Coudert et al, as it is not observed in any other of the comparisons below which include the same bands. Such behavior has previously been shown to be the consequence of using effective Hamiltonians to represent intensities [60]. Figure 3a compares 4993 transitions provided in the study of Birk et al [7], which contains measurements from several experiments in the regions of 1250 -1750 cm −1 [34], 1850 -2280 cm −1 [6], 2390 -4000 cm −1 [6] and 4190 -4340 cm −1 [35].…”
Section: H 2 16 Omentioning
confidence: 91%
“…Although TCCON is not a solely HITRAN-based analysis , a correction factor of 0.9898 for CO 2 , 0.9765 for CH 4 , and 1.0183 for H 2 O (Wunch et al, 2010) is needed to bring the overall TCCON retrievals into agreement with the WMO-based data. Additionally, theoretical calculations by Zak et al (2016) found an approximately 0.5 % difference between CO 2 line parameters from HITRAN 2012 and their density functional theory calculations and an additional 0.5 % difference between the calculations and new measurements by Devi et al (2016) in the 1.6 µm region. Certainly this discrepancy between retrievals from HITRAN- and WMO-calibrated instruments is not fundamental, and further experimental work should lead to improved spectral database parameters and much better agreement.…”
Section: Comparison Of Open-path Dcs To a Crdsmentioning
confidence: 93%